2439. Outcomes of Minocycline Use on Gram-Negative Infections and Implications of MIC. (26th November 2018) - Cheng, Jennifer; Kubin, Christine J
Abstract: Background: Minocycline (MINO) is a treatment option for Acinetobacter baumannii and Stenotrophomonas maltophilia infections due to high in vitro susceptibility. Literature suggests it may also be an option for carbapenamase-producing enterobacteriaceae. MINO minimum inhibitory concentrations (MICs) vary by organism and dosing varies by center. Additional data are needed to assess MINO effectiveness in Gram-negative infections and determine if a relationship exists between MIC and treatment outcomes. Methods: Retrospective study evaluating MINO use in adults at NewYork-Presbyterian Hospital from 2012 to 2017. Patients included received MINO ≥2 days for a culture-positive Gram-negative infection (CDC/NHSN criteria) susceptible to MINO. Patients with MINO started >5 days after positive culture or with untreated polymicrobial infections were excluded. The primary outcome was clinical failure at the end of therapy. Secondary outcomes included 30-day mortality, development of resistance or recurrence within 90 days. Results: 114 patients were included: majority were male (51%) with median age 57 years. Median duration was 12 days with 8 patients receiving high-dose MINO (≥150 mg q12H). S. maltophilia was the most prevalent pathogen (72%) followed by Klebsiella pneumoniae (16%) with a median MINO MIC of 1 mg/L. 68% of patients received combination therapy. Treatment success was observed in 71 patients (63%). Patients with treatment failure had higher median Charlson Comorbidity Index (5 vs. 3; P = 0.026), SOFA score (7 vs. 5; P = 0.028), and were more likely to have underlying leukemia or lymphoma (39% vs. 7%; P < 0.001). No differences were seen in primary or secondary outcomes between combination and monotherapy regimens. MICs had no impact on failure outcome, 30-day mortality or 90-day recurrence (all P > 0.05); however, MICs ≤ 2 mg/L were associated with increased development of resistance (34% vs. 12%; P = 0.021). In a multivariable analysis, vasopressor use (OR 2.79; 95% CI 1.05, 7.41; P = 0.04) and underlying leukemia/lymphoma (OR 4.49; 95% CI 1.26, 15.95; P = 0.02) were associated with increased risk of treatment failure. Conclusion: MINO MIC impacted resistance, but did not correlate with treatment failure, mortality or recurrence. Severity of illness and comorbidities but not choice of MINO may be associated with clinical failures. Disclosures: All authors: No reported disclosures.